(untitled) (Journal of Atomic and Molecular Sciences, 2015)
The molecular geometries, spectroscopy constants, and anharmonic force field of hypochlorous acid have been calculated at B3PW91, MP2, CCSD(T) levels of theory employing three basis sets, 6-311g(3df,2p), 6-311g(3df,3pd) and cc-pVQZ, respectively. The equilibrium structures, rotational constants, anharmonicity constants, vibration-rotation interaction constants, quartic and sextic centrifugal distortion constants are compared with the available experimental data. Coriolis coupling constants are also calculated here. The partial spectroscopy constants show that the MP2 represent an improvement over the results obtained from B3PW91. The CCSD(T) method is also a good choice to study the anharmonic force field of this molecule.